Using the power card strategy to teach poison-prevention skills to children with developmental disabilities. - Kutlu, Metehan; Berk, Savas (International Journal of Developmental Disabilities, 2025)
The purpose of this study was to evaluate the power card strategy (PCS) in teaching children with developmental disabilities (DD) how to respond safely to the presence of cleaning chemicals. One female and two male participants with DD, aged 8–14, took part in the study, which was conducted using a multiple-probe-across-participants design. The study's findings showed that the PCS was effective in teaching poison prevention skills to children with DD. All the participants were able to learn the target skill and maintain and generalize their learning. Social validity data were also collected from participants, their parents, and teachers. Social validity findings indicated that the opinions of the participants, their parents, and teachers were positive overall. Implications for instruction and future research are discussed based on the results of the study.